High Utility Itemset Mining: A Thorough Examination of Data Mining Methods, Algorithms, and Uses - Dharmbir, Ram Kinkar Pandey, Rajiv Kumar, (Journal of Computational Analysis and Applications (JoCAAA), 2024)
The High Utility Itemset Mining (HUIM) is an important revolution in the data mining world as itprovides organizations and researchers with the option of mining patterns that are not onlycommon but also profitable and relevant in the context. A distinction between the HUIM andtraditional association